Impact of foreign direct investment on Thailand's trade and domestic private investment : a thesis presented in partial fulfilment of the requirements for the degree of Master in Applied and International Economics at Massey University - Vaninthorn, Hongskul (Massey University, 2000)
Foreign investment not only brings along the direct benefits to the host country in the form of technological progress, but it also stimulates domestic activities through the linkage effects. This study investigates the impact of foreign direct investment (FDI) on Thailand's imports, exports, and domestic private investment, covering the period 1965 to 1997. By using the method of autoregressive distributed lag (ARDL) that minimises the possibility of estimating spurious relations while retaining long-run relationship information, the empirical results indicate that FDI does have significant effects on imports and domestic private investment, but not on exports. The vector error correction model (VECM) analysis, variant of the vector autoregression (VAR) analysis, is applied to investigate the inter-relation between trade (imports and exports), domestic private investment, and FDI. Through the impulse response approach, the results show that an increase in one variable does have an impact on others. On average, the impact will last for eight years. The empirical results from forecast error variance decomposition analysis also indicate that imports, exports, domestic private investment, and foreign direct investments have inter-relations between themselves.
Keywords: Foreign investments, Thailand; Investments, Thailand; Economic conditions, Thailand; Commerce, Thailand